The Role of Dystopian Art in the Climate Crisis - Nielsen, Kim Skjoldager (Peripeti, 2020)
Skjoldager-Nielsen discusses how dystopian works of art can compell us to act and hope in spite of the paralyzing horizon of the climate crisis.